Pengembangan Filsafat Ilmu dalam Manajemen Era Digitalisasi - Alicia Hanna Fadilla; Susi Yusfika Panjaitan; Fahmi Azhar Nasution; Muhammad Dahriansyah; Siti Mujiatun (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research discusses the development of philosophy of science in the context of management science in the era of digitalization. With a qualitative approach, this research identifies the role of philosophy of science as a conceptual foundation in facing the challenges of the digital era, such as automation, big data and artificial intelligence. This study outlines the three main pillars of the philosophy of science, namely ontology, epistemology and axiology, and their application in the development of management theory and practice. The research results show that integrating the philosophy of science in management can increase adaptability, innovation and ethics in organizational management in the digital era. This research recommends strengthening management education based on the philosophy of science to produce leaders who are competent and broad-minded